Analisis Semiotika Nilai Moral dan Budaya Film Ngeri – Ngeri Sedap - Afdal Rizki I (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to determine how moral and cultural values ​​are formed in the Ngeri-ngeri sedap film. This study uses a descriptive research type. The results of this study discuss several scenes related to the issue of family conflict in the Ngeri-Ngeri Sedap film. The issues include: parents who have the right to control their children, parents who tell their children to marry fellow Batak people to continue the culture, parents who tell their children to return from their travels, the cause of family conflict because each family member feels like they want to be heard but doesn't want to hear, and the role and opinions of women in this family are not considered. The relationship in the family is very eternal and eternal, therefore every conflict in the family must be resolved so that a harmonious family is realized.